PERBEDAAN POLA RESISTENSI Staphylococcus koagulase negatifISOLAT DARAH TERHADAP ANTIBIOTIKA DI RSU Dr SAIFUL ANWAR MALANG TAHUN 2000-2001 DENGAN 2004-2005 - Dzen, Sjoekoer M.; Santoso, Sanarto; Roekistiningsih, Roekistiningsih; Santosaningsih, Dewi (Jurnal Kedokteran Brawijaya, 2005)
Coagulase negative staphylococci (CoNS) are the common bacterias causing hospital-acquired infection manifested as bacteremia. The antibiotics therapy against bacterial infection is mostly empiric, whereas the bacterial pattern and its sensitivity to antibiotics differ between region and from year to year. The objective of this study wasto determine the changes of prevalence and antibiotics sensitivity pattern of CoNS, the etiologic agent of bacteremia in patients hospitalised in Dr.Saiful Anwar General Hospital, Malang. Culture and antibiotic sensitivity test wereperformed on 650 and 1063 blood samples during the year of 2000-2001and 2004-2005 respectively in the Laboratory of Microbiology, Faculty of Medicine, Brawijaya University / Dr.Saiful Anwar General Hospital in Malang following NCCLS  1997. ChiSquare test was used to analysed of data. The result of this study revealed that the CoNS was the most isolate found in the blood samples and its resistance to beta lactam antibiotics tends to increase statistically. Key words:Coagulase negative staphylococci, antibiotics sensitivity pattern